Long-Term Effects of Perinatal Exposure to a Glyphosate-Based Herbicide on Melatonin Levels and Oxidative Brain Damage in Adult Male Rats - Daiane Cattani; Paula Pierozan; Ariane Zamoner; Eva Brittebo; Oskar Karlsson (MDPI AG, 2023)
Concerns have been raised regarding the potential adverse health effects of the ubiquitous herbicide glyphosate. Here, we investigated long-term effects of developmental exposure to a glyphosate-based herbicide (GBH) by analyzing serum melatonin levels and cellular changes in the striatum of adult male rats (90 days old). Pregnant and lactating rats were exposed to 3% GBH (0.36% glyphosate) through drinking water from gestational day 5 to postnatal day 15. The offspring showed reduced serum melatonin levels (43%) at the adult age compared with the control group. The perinatal exposure to GBH also induced long-term oxidative stress-related changes in the striatum demonstrated by increased lipid peroxidation (45%) and DNA/RNA oxidation (39%) together with increased protein levels of the antioxidant enzymes, superoxide dismutase (SOD1, 24%), glutamate-cysteine ligase (GCLC, 58%), and glutathione peroxidase 1 (GPx1, 31%). Moreover, perinatal GBH exposure significantly increased the total number of neurons (20%) and tyrosine hydroxylase (TH)-positive neurons (38%) in the adult striatum. Mechanistic in vitro studies with primary rat pinealocytes exposed to 50 µM glyphosate demonstrated a decreased melatonin secretion partially through activation of metabotropic glutamate receptor 3 (mGluR3), while higher glyphosate levels (100 or 500 µM) also reduced the pinealocyte viability. Since decreased levels of the important antioxidant and neuroprotector melatonin have been associated with an increased risk of developing neurodegenerative disorders, this demonstrates the need to consider the melatonin hormone system as a central endocrine-related target of glyphosate and other environmental contaminants.